THE INFLUENCE OF WORLD OIL AND NATURAL GAS PRICE ON INDONESIAN FINANCIAL STOCKS AND EXCHANGE RATE DURING THE RUSSIA-UKRAINE GEOPOLITICAL CONFLICT - Dewanto Alfarizmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Geopolitical conflict of Russia and Ukraine in the early 2022 has been significantly impacting global oil and gas price. Indonesia, as net oil importer country are highly affected by the changes of these price. This study investigates the impact of world oil and natural gas price, Indonesian exchange rate, and stock price of financial sector companies listed in IDX. Data analysis was conducted using Multiple Linear Regression (MLR) and Structural Equation Modeling (SEM) were used to find the interrelationship between variables. This study uses stock price of major financial corporation listed in IDX on the period of 2021 to 2024 as representative indicator of market response. Results show that world oil and natural gas has no simultaneous impact on financial stock price, but has simultaneous impact on Indonesian exchange rate. Result also show that individual impact of world oil price on exchange rate is significant and the impact of exchange rate on financial stock price are moderate. These finding suggest investor and other stakeholder to monitor and studying the impact of global commodity and exchange rate when planning to invest in financial stocks.